The effects of care provided in: "mother" - infant attachment in infants lived in "Metera" babies center - Βορριά, Π.; Σαραφίδου, Ε.; Παπαληγούρα, Ζ.; Λαμπίδη, Α.; Κοντοπούλου, Α. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF